Bride Of His Choice. - Darcy, Emma; Mills & Boon Classics (Sydney, New South Wales : HarperCollins Publishers, 2024)
A marriage of convenience. Five sisters...and Richard Seymour has to marry one to gain control of the Durant financial empire. Made to feel the ugly duckling by her glamorous family, and totally rejected by her father, Leigh Durant is stunned when Richard makes his choice — to marry her! Can he possibly give her the sense of belonging and love she’s always craved? His proposition is very tempting. And they do share an intense physical attraction. But is she truly the bride he wants...or just the easiest path to power?.
General
Keywords: Contemporary romance; Fiction - Romance - Contemporary; Electronic books